Dimensions of Migrant Integration in Western Europe - Heath, Anthony F.; Schneider, Silke L. (Frontiers in Sociology, 2021)
The integration of immigrant minorities is a major concern for diverse societies – with major implications for the well-being of those affected, social cohesion and group relations, and economic and social progress. In this paper, we give a comprehensive description of long-term migrant integration in Western Europe to investigate theories of migrant assimilation and integration. We take a multidimensional approach, looking at 10 indicators measuring social, structural, political, civic and cultural integration. We take an innovative approach to measuring minority background by using two complementary measures: generational status, distinguishing first and second-generation migrants from the third and higher up ‘natives’, and self-reported ancestry, separating those with autochthonous-only ancestry from those with various kinds of allochthonous ancestry. Using interaction effects between these measures, we can test whether generational change is faster or slower for some ethnic groups than for others, i.e. whether different groups integrate at differing speeds. Using the pooled samples of all Western European countries included in the European Social Survey (ESS) rounds 7 and 8, we run multivariate regression analyses to estimate the effects of migrant background on the 10 indicators of integration. Compared to migrants with autochthonous ancestry, respondents of Middle Eastern, North African & Central Asian as well as Sub-Saharan African ancestry are less integrated on all dimensions of integration except the political and civic ones. The South & South-East Asian group is also substantially less assimilated socially and culturally, but not so much structurally. They are closely followed by the South East and East European groups, following the same pattern except that the latter are less integrated politically as well. We only find substantial interaction effects between ethnic group and migrant generation for two integration indicators, namely citizenship and homophobia, for which speed of integration thus appears to differ across ethnic groups. For all other indicators, integration speed does not appear to differ across ethnic groups, supporting straight line assimilation theory, with social integration in terms of interethnic friendship potentially rather following a 'bumpy-line' pattern.